Royal seal of Chhatrapati Shivaji Maharaj - Ghosh, Ayan (2023)
Seal (Rajmudra) of Chhatrapati Shivaji Maharaj at the base of the Jijamata memorial. The Sanskrit text is as follows: प्रतिपच्चन्द्रलेखेव वर्धिष्णुर्विश्ववन्दिता | शाहसूनो: शिवस्यैषा मुद्रा भद्राय राजते ||